Evaluating Use of Curcumin with Antioxidants in Oral Submucous Fibrosis. A Clinical Study - Singh Narwariya, Ravindra; Kumar, Mayank; Baroi, Abhijit; Saluja, Sonali; Dixit, Sumit; Jain, Vidhi (Journal of Neonatal Surgery, 2025)
Background: Oral Submucous Fibrosis (OSMF) is a chronic, progressive, and potentially malignant disorder characterized by fibrosis of the oral mucosa, leading to restricted mouth opening and burning sensations. Curcumin, a bioactive compound derived from turmeric, exhibits anti-inflammatory and antifibrotic properties. This study evaluates the effectiveness of curcumin combined with antioxidants in managing OSMF symptoms and improving mouth opening. Materials and Methods: A randomized clinical study was conducted on 60 patients diagnosed with OSMF. Participants were divided into two groups: Group A (n=30) received curcumin (300 mg/day) with antioxidants, while Group B (n=30) received only antioxidants. The treatment duration was 12 weeks, and assessments were conducted at baseline, 6 weeks, and 12 weeks. Parameters evaluated included mouth opening (measured in mm), burning sensation (assessed using a Visual Analog Scale), and mucosal flexibility. Data were statistically analyzed using paired and unpaired t-tests. Results: At the end of 12 weeks, Group A showed a significant improvement in mouth opening (increase of 5.2 ± 1.3 mm) compared to Group B (2.8 ± 0.9 mm). Burning sensation scores reduced significantly in Group A (from 7.2 ± 1.1 to 2.3 ± 0.9) compared to Group B (from 7.0 ± 1.0 to 4.6 ± 1.2). Additionally, mucosal flexibility improved in 80% of patients in Group A versus 50% in Group B. The differences between groups were statistically significant (p < 0.05). Conclusion: The findings suggest that curcumin, when combined with antioxidants, significantly enhances mouth opening, reduces burning sensation, and improves mucosal flexibility in OSMF patients compared to antioxidants alone. Curcumin's anti-inflammatory and antifibrotic properties make it a promising adjunctive therapy for OSMF management. Further large-scale studies are warranted to confirm these findings.